Primary management of burn injuries: Balancing best practice with pragmatism - Nikki L. Allorto (South African Family Practice)
Management of burns is an often-neglected area in training from undergraduate to specialist level. There is, however, a high burden of injury that affects a largely vulnerable population, for example, children, the elderly and epileptics. This CPD article highlights that first aid should include cooling the burn with cool running tap water up to 3-hours post injury (Burnshield may be used if cool running water is not available); removal of all blisters facilitates accurate assessment of the burn size and depth; formulas exist for the resuscitation of acute burn injuries of more than 10% – 15% total body surface area and prophylactic antibiotics should not be administered to patients with acute burns as the prevention of infection should lie with good wound care (including good wound cleaning and the use of topical antimicrobial dressings). A standardised approach to pain management with an incremental pharmacological approach should be followed whilst considering other issues such as neuropathic pain, anxiety and depression.